العنف في المؤسسات التربوية الجزائرية دراسة في البنية والحلول - كريفيف, مريم (جامعة الوادي - University of Eloued, 2022)
برزت ظاهرة العنف في الوسط المدرسي بشكل كبير في جميع المستويات المدرسية ، ومتمثل في ممارسة أشكال العنف بأشكاله: العنف اللفظي والجسدي والرمزي ،مما يعيق وظيفة التعليم والتعلم ، وتهدف هذه الدراسة إلى التعرف على أسباب العنف في الوسط المدرسي وعلى موضوع الوقاية من حدته من خلال وضع أسس أو استراتجيات لتعزيز الجانب الوقائي بالمدارس وحماية التلميذ من هذه الآفة المدرسية ، والتي أصبحت محط اهتمام الأسرة التربوية بسبب انزعاجهم وخوفهم على أمن وسلامة أبنائهم ومحور اهتمام القائمين على العملية التربوية في الجزائر . Abstract: The phenomenon of violence in the school environment has emerged significantly at all school levels, and is represented in the practice of violence in all its forms: verbal, physical and symbolic violence, which hinders the function of teaching and learning. Foundations or strategies to enhance the preventive aspect in schools and protect the student from this school scourge, which has become the focus of the educational family's attention because of their annoyance and fear for the safety and security of their children and the focus of attention of those in charge of the educational process in Algeria.
مقال
Keywords: عنف , مؤسسة تربوية, أسرة ,سلوك; violence, educational institution, family, behavior